THE POLEMIC OF GIVING DIRECT EFFECT OF WTO LAW AND DSB DECISION TO DOMESTIC LAW FOR INDIVIDUAL’S JUDICIAL PROTECTION - Intan Soeparna (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
The main objective of WTO Law is to accommodate individual’s right in order to obtain better benefit of international trade. However, when a government violates WTO Law, it is therefore causing deprivation of individual right itself. Direct effect seems to be a feasible doctrine to provide a judicial protection for individual, in order to rebalance the right that is violated. Nevertheless, this doctrine is intractable to imply. This article discuss the polemic of giving direct effect of WTO Law and DSB Decision to domestic law to provide judicial protection for individual who becomes victim of WTO violation conducted by government Tujuan aturan WTO adalah mengakomodasi hak individu untuk memperoleh keuntungan dalam perdagangan internasional, akan tetapi ketika pemerintahnya melanggar aturan WTO, maka akan menyebabkan pelanggaran hak. Oleh karena itu, doktrin direct effect aturan WTO dapat menjadi doktrin yang memberikan perlindungan hukum, dalam rangka menyeimbangkan hak yang dilanggar. Namun, doktrin ini sangat sulit diterapkan, oleh karena itu, artikel ini mendiskusikan polemik dalam menerapkan doktrin direct effect. Aturan WTO dan keputusan DSB agar pemerintah dapat memberikan perlindungan hukum pada individu yang menjadi korban pelanggaran aturan WTO.